MEDIA PEMBELAJARAN INTERAKTIF DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA - Fuji Lestari; Nadia Vega; Muhamad Sudharsono; Tengku Reynaldi Riansyah; Syifani Nur Aliifah; Vanny Najwa Saphira (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Education is a crucial foundation in determining the future of a nation, and students' enthusiasm for learning is a vital component in the learning process. A strong spirit not only improves academic results but also fosters a continuous interest in learning. With the development of information and communication technology, interactive learning media has become an important tool to encourage students' learning enthusiasm. This medium functions as an assistive technology that supports students in the learning process, personal development, and assessment of their abilities. By combining multimedia elements and interaction, this learning media offers an engaging learning experience that aligns with the characteristics of the digital generation. The method applied in this research is a literature review, which collects and analyzes various scientific references regarding interactive learning media. The research results show that the utilization of various types of media, such as interactive games, applications based on Lectora Inspire, and augmented reality-based media, can enhance students' learning motivation by creating engaging and interactive learning experiences. Interactive learning media not only capture students' attention but also stimulate their participation in the learning process. Thus, interactive learning media can be an effective solution in enhancing students' enthusiasm and learning outcomes, as well as helping them understand the material better.